The Integrated Programme for Commodities - I. S. Chadha (Intereconomics, 1979)
The fifth session of the United Nations Conference on Trade and Development in Manila will undertake a detailed review of the progress in the implementation of the Integrated Programme for Commodities. I. S. Chadha attempts such a review from the point of view of UNCTAD for our readers.
Keywords: 330; Unctad V